Information and globalization / Norshahiba Mohamad Salleh - Mohamad Salleh, Norshahiba (Faculty of Information Management, 2015)
Through the times does fly, information has been changed tremendously with the development of information technology. Information has been recorded by sculptured on the rocks to the advancement speed of Internet medium like blogs and social networking. The intensity of Internet has gone globalized which the information can be transferred easily and in the rapid time across the world's continent. Even the simple text or the conversation can be applied too!